Functional Analyses of House Fly Carboxylesterases Involved in Insecticide Resistance - Xuechun Feng; Xuechun Feng; Nannan Liu (Frontiers in Physiology, 2020)
Carboxylesterase-mediated metabolism is one of major mechanisms involved in insecticide resistance. Our previous study has identified multiple carboxylesterase genes with their expression levels were significantly upregulated in pyrethroid resistant house flies. To further explore their metabolic functions, we used insect Spodoptera frugiperda (Sf9) cells to express these carboxylesterases in vitro and measure their hydrolytic activities toward esterase substrates. Our results indicated that these carboxylesterases can efficiently hydrolyze α-naphthyl acetate rather than β- naphthyl acetate. A cell based MTT cytotoxicity assay indicated that carboxylesterase-expressing cells show enhanced tolerance to permethrin, suggesting important roles of these carboxylesterases in metabolizing permethrin and thereby protecting cells from permethrin treatments. The metabolic functions of carboxylesterases were further verified by conducting in vitro metabolism studies toward permethrin and its potential metabolites 3-phenoxybenzyl alcohol and 3-phenoxybenzaldehyde, which not only suggested the potential metabolic pathway of permethrin in insects, but also important roles of these candidate carboxylesterases in metabolizing permethrin and conferring resistance in house flies. Homology modeling and docking were finally conducted to reflect interactions between permethrin ligand and carboxylesterase proteins, visually confirming the metabolic functions of carboxylesterases to insecticides in house flies.